2015
DOI: 10.5586/asbp.2015.002
|View full text |Cite
|
Sign up to set email alerts
|

Acid α-galactosidase is involved in D-chiro-inositol accumulation during tartary buckwheat germination

Abstract: Tartary buckwheat seed and especially its sprouts are rich in D-chiro-inositol (DCI). The research was to evaluate when DCI was most accumulated in tartary buckwheat sprouts. In addition, we explored the activity and expression pattern of α-galactosidase during tartary buckwheat seed germination. The results showed that DCI contents steadily increased at early stage of germination and reached the highest level of 33.42 µg/seed at 24 h during the 72 h trail. However, the total fagopyritol contents sharply decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…While germination under light and dark conditions does not seem to affect the GOS degradation (Vidal-Valverde et al, 2002), the extent of the degradation directly correlates with the germination time, as the content of oligosaccharides constantly decreases (Wang et al, 1997). Germination has also been shown to be effective in the reduction of GOS in cereals and pseudo cereals, as well as other α-galactosides, such a fagopyritols in buckwheat (Gamel et al, 2006;Harris & MacWilliam, 1954;Horbowicz et al, 1998;Jia et al, 2015;MacWilliam et al, 1956). Despite a large number of studies reporting a significant reduction of GOS upon 2−6 days of germination, Tuck et al (2018) observed elevated GOS levels in sprouted chickpeas.…”
Section: Activation Of Endogenous Seed-enzymesmentioning
confidence: 99%
“…While germination under light and dark conditions does not seem to affect the GOS degradation (Vidal-Valverde et al, 2002), the extent of the degradation directly correlates with the germination time, as the content of oligosaccharides constantly decreases (Wang et al, 1997). Germination has also been shown to be effective in the reduction of GOS in cereals and pseudo cereals, as well as other α-galactosides, such a fagopyritols in buckwheat (Gamel et al, 2006;Harris & MacWilliam, 1954;Horbowicz et al, 1998;Jia et al, 2015;MacWilliam et al, 1956). Despite a large number of studies reporting a significant reduction of GOS upon 2−6 days of germination, Tuck et al (2018) observed elevated GOS levels in sprouted chickpeas.…”
Section: Activation Of Endogenous Seed-enzymesmentioning
confidence: 99%
“…44 These polyphenols are involved in several physiological activities, such as antioxidation, 9 lipid-lowering, 46,47 hypoglycaemia, 48 and prevention of cardiovascular 49 and cerebrovascular diseasess. 50 The CCLG sugar alcohols are mainly chiral inositol and its galactosides, which are mainly found in buckwheat 51 and mung beans. 52 D-Chiral inositol has the physiological function of promoting liver lipid metabolism, antioxidation, anti-aging, and anti-inflammation.…”
Section: ■ Nutrition and Phytochemicals Of Cclgsmentioning
confidence: 99%
“…These polyphenols are involved in several physiological activities, such as antioxidation, lipid-lowering, , hypoglycaemia, and prevention of cardiovascular and cerebrovascular diseasess . The CCLG sugar alcohols are mainly chiral inositol and its galactosides, which are mainly found in buckwheat and mung beans .…”
Section: Nutrition and Phytochemicals Of Cclgsmentioning
confidence: 99%